La poesía latina en el contexto amoroso de la comedia elegíaca medieval: Catulo y Ovidio en el De tribus puellis - Arcaz Pozo, Juan Luis (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
This article studies the presence of basia mille and the écfrasis topic of Catulls poems 5 and 64, respectively, and the elegy I 5 of Ovids Amores into the elegiac comedy De tribus puellis. The two classics poets offers to anonym author of the comedy the theme of amorous context that describes into their work.